Translating Cultural References In Children’s Literature (Revue El-Wahat pour les Recherches et les Etudes, 2021)
Translating Children’s literature plays an important role in helping children develop their knowledge and discover other people’s societies and culture, since literature is the mirror of the society to which it belongs. Yet, transferring cultural references in children’s literature from a language to another is a challenging task for translators particularly with the existence of a cultural gap between the source culture and the target one. This study attempts to shed some light on the issue of translating cultural references by analyzing some examples taken from two Arabic translations of Mark Twain’s novel “The Adventures of Tom sawyer”.Key words- Translation, children’s literature, cultural references, adaptation, literality.